Cochlear Implant Electrode Effect on Sound Energy Transfer Within the Cochlea During Acoustic Stimulation. Issue 9 (October 2015) - Greene, Nathaniel T.; Mattingly, Jameson K.; Jenkins, Herman A.; Tollin, Daniel J.; Easter, James R.; Cass, Stephen P.
<x xml:space="preserve">Abstract</x> Hypothesis: Cochlear implants (CIs) designed for hearing preservation will not alter mechanical properties of the middle and inner ears as measured by intracochlear pressure (PIC) and stapes velocity (Vstap). Background: CIs designed to provide combined electroacoustic stimulation are now available. To maintain functional acoustic hearing, it is important to know if a CI electrode can alter middle or inner ear mechanics because any alteration could contribute to elevated low-frequency thresholds in electroacoustic stimulation patients. Methods: Seven human cadaveric temporal bones were prepared, and pure-tone stimuli from 120 Hz to 10 kHz were presented at a range of intensities up to 110 dB sound pressure level. PIC in the scala vestibuli (PSV) and tympani (PST) were measured with fiber-optic pressure sensors concurrently with VStap using laser Doppler vibrometry. Five CI electrodes from two different manufacturers with varying dimensions were inserted via a round window approach at six different depths (16–25 mm). Results: The responses of PIC and VStap to acoustic stimulation were assessed as a function of stimulus frequency, normalized to sound pressure level in the external auditory canal, at baseline and electrode-inserted conditions. Responses measured with electrodes inserted were generally within approximately 5 dB of baseline, indicating little effect of CI electrode insertion on PIC and VStap. Overall, mean differences across conditions were small for all responses, and no substantial differences were consistently visible across electrode types. Conclusion: Results suggest that the influence of a CI electrode on middle and inner ear mechanics is minimal despite variation in electrode lengths and configurations.